2013
DOI: 10.1089/scd.2012.0082
|View full text |Cite
|
Sign up to set email alerts
|

An In Vitro Model of Developmental Synaptogenesis Using Cocultures of Human Neural Progenitors and Cochlear Explants

Abstract: In mammals, the sensory hair cells and auditory neurons do not spontaneously regenerate and their loss results in permanent hearing impairment. Stem cell therapy is one emerging strategy that is being investigated to overcome the loss of sensory cells after hearing loss. To successfully replace auditory neurons, stem cell-derived neurons must be electrically active, capable of organized outgrowth of processes, and of making functional connections with appropriate tissues. We have developed an in vitro assay to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
55
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(60 citation statements)
references
References 53 publications
5
55
0
Order By: Relevance
“…Recent literature supports the use of neural crest progenitors in a cell replacement therapy for deafness, given the molecular similarity of this population to placode-derived sensory neurons (Huisman and Rivolta, 2012;Nayagam et al, 2013). In addition, we have recently demonstrated that neurons derived from this induction protocol express key auditory neural proteins including NeuroD1, Brn3a, GATA3, Islet1 and neurofilament ( Fig.…”
Section: Introductionmentioning
confidence: 58%
See 2 more Smart Citations
“…Recent literature supports the use of neural crest progenitors in a cell replacement therapy for deafness, given the molecular similarity of this population to placode-derived sensory neurons (Huisman and Rivolta, 2012;Nayagam et al, 2013). In addition, we have recently demonstrated that neurons derived from this induction protocol express key auditory neural proteins including NeuroD1, Brn3a, GATA3, Islet1 and neurofilament ( Fig.…”
Section: Introductionmentioning
confidence: 58%
“…A number of studies have now demonstrated the potential of stem cells to differentiate into appropriate neurosensory progenitors, including those of human origin (Shi et al, 2007;Chen et al, 2009Chen et al, , 2012Nayagam et al, 2013). The expression of key developmental markers in the differentiation of human stem cells toward an auditory neural lineage has recently been documented (Chen et al, 2012; and reviewed by Gunewardene et al, 2012) and includes the expression of key proteins and transcription factors Sox 2, Pax2/8, FoxG1, Six1, Nestin and Brn3a (Chen et al, 2012), Brn3a, GATA3 and peripherin (Shi et al, 2007), Pax2, Brn3a, peripherin, and neurofilament and NeuroD1, Brn3a, GATA3, Islet1, peripherin, and neurofilament (Gunewardene et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In an in vitro study, neural precursors derived from hESCs were cultured along with cochlea in the 3D culture medium and it was observed that the precursor neurons were electrically active and they could differentiate into the sensory HC alongside the implanted cochlea. These results showed that neural precursors derived from hESCs might be useful in developing treatments that could directly replace the ANs [79].…”
Section: Three-dimensional Culture Systemmentioning
confidence: 84%
“…Although the strategies to date remain relatively ineffi cient in terms of cell yield, a number of laboratories have been successful in generating cells with molecular and functional phenotypes resembling sensory hairlike cells from ES cells and from terminally differentiated cells such as fi broblasts from mouse and human (e.g., Koehler et al 2013 ;Ouji et al 2013 ;Ronaghi et al 2014 ). Similar studies have been used to generate neuronal cells with characteristics of spiral ganglion neurons (e.g., Tong et al 2010 ;Nayagam et al 2012 ). Successful reprogramming of cells from humans carrying highly penetrant Mendelian mutations or lower penetrance risk variants should permit in-depth analysis of pathways associated with inner ear dysfunction in a cellular context that better approximates conditions in vivo.…”
Section: Human Genetic Studiesmentioning
confidence: 99%